Teenage childbirth and young adult criminal convictions: A quasi-experimental study of criminal outcomes for teenage mothers - Coyne, Claire A. (2013)
PURPOSE: Teenage childbirth is associated with poor psychosocial outcomes for teen mothers. One example is that teen mothers have higher rates of antisocial behavior. The extant research has not been able to determine if teenage motherhood is independently associated with criminal behavior, or if the association is due to selection factors associated with both teenage childbirth and criminal behavior. METHODS: We used longitudinal data from Swedish national registers and sibling-comparisons (both full- and half-siblings) to identify the extent to which there is an independent association between teenage childbirth and mothers’ likelihood of criminal conviction between ages 20-30, or if the association is confounded by familial (including genetic or environmental) factors that make sisters similar. RESULTS: Women who began childbearing as teenagers were more likely to be convicted of a crime in young adulthood compared to women who delayed childbearing. When sisters were compared, the association between teenage childbirth and criminal convictions disappeared. Multivariate behavior genetic analyses suggest genetic and shared environmental account for the association. CONCLUSIONS: The statistical association between teenage childbirth and early adulthood criminal convictions is confounded by genetic and shared environmental factors that influence both the likelihood of teenage childbirth and risk of early adulthood criminal conviction.